Complete genome sequence of Nitrosomonas sp. Is79, an ammonia oxidizing bacterium adapted to low ammonium concentrations. Issue 3 (November 2013) - Bollmann, Annette; Sedlacek, Christopher; Norton, Jeanette; Laanbroek, Hendrikus; Suwa, Yuichi; Stein, Lisa; Klotz, Martin; Arp, Daniel; Sayavedra-Soto, Luis; Lu, Megan; Bruce, David; Detter, Chris; et al.
Abstract Nitrosomonas sp. Is79 is a chemolithoautotrophic ammonia-oxidizing bacterium that belongs to the familyNitrosomonadaceae within the phylumProteobacteria . Ammonia oxidation is the first step of nitrification, an important process in the global nitrogen cycle ultimately resulting in the production of nitrate.Nitrosomonas sp. Is79 is an ammonia oxidizer of high interest because it is adapted to low ammonium and can be found in freshwater environments around the world. The 3, 783, 444-bp chromosome with a total of 3, 553 protein coding genes and 44 RNA genes was sequenced by the DOE-Joint Genome Institute Program CSP 2006.